Documentation, anti-aging activities and phytochemical profiling of selected medicinal plants used by Jakun women in Kampung Peta, Mersing, Johor - Ismail, Nur Amalina (2017)
Traditional knowledge of indigenous people could become the baseline information for the discovery of anti-aging agent. The objectives of this study were to document the knowledge of Jakun people in Kampung Peta, Mersing, Johor on medicinal plants for women’s healthcare; to investigate the optimal formulations of herbal mixture used by Jakun women based on phytochemicals content and antioxidant activity; to determine the anti-aging potential of the selected formulations; and to investigate the major phytochemical constituents in the formulations. Based on qualitative analysis from semi-structured interview, twelve species of medicinal plants have been documented for women’s healthcare. Among species documented, four species, Cnestis palala (Pengesep), Urceola micrantha (Serapat), Labisia pumila (Kacip fatimah) and Microporus xanthopus (Kulat kelentit kering) that were prepared in the form of mixture have been used for formulation study. About 24 formulations have been developed from the simplex centroid design and tested for total phenolic content (Folin-Ciocalteu method), total flavonoid content (aluminium chloride colorimetric method) and three different antioxidant assays (DPPH scavenging, ABTS decolourization and FRAP assays). Single formulation of Cnestis palala, single formulation of Urceola micrantha and binary mixture of C. palala and U. micrantha are among the optimal formulations with high phytochemicals content and antioxidant activities that were further evaluated for anti-aging activities. For anti-aging activities, five enzymatic assays have been tested on the three formulations which are matrix metalloproteinase-1 (MMP-1) inhibition, elastase inhibition, tyrosinase inhibition, acetyl- and butyrylcholinesterase inhibition assays. Single formulation of U. micrantha showed the highest inhibition towards MMP-1 (49.44 ± 4.11 %) and elastase enzymes (20.33±2.52%), while single formulation of C. palala showed highest inhibitions towards tyrosinase (14.06±0.31%), acetylcholinesterase (32.92±2.13%) and butyrylcholinesterase (34.89±2.84%) enzymes. The identification of phytochemicals compound have been carried out using gas chromatography-mass spectrometer (GC-MS), which showed the presence of 2,2-dimethoxybutane and 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP) in the three formulations extract. The presence of catechol and quinic acid in U. micrantha extract might possibly contribute to anti-aging activities of the extract. These findings could become baseline for the exploration of novel anti-aging agents from natural source by using the traditional knowledge of indigenous people.